THE UNFAIR TREATMENT ISSUES TOWARDS AFRICAN-AMERICAN WOMEN AS PORTRAYED IN HIDDEN FIGURES FILM - Sari, Indah; Surya, Satyawati; Muhajir, Fatimah (Fakultas Ilmu Budaya Universitas Mulawarman, 2022)
This study describes the types of gender discrimination and racial discrimination that are obtained by African-American women characters the in Hidden Figures film. In order to describe the two unfair treatments, this study uses two theories such as Lorber’s gender inequality and Miles’ racism. The research design was descriptive qualitative. The data of this study were taken from Hidden Figures film in the forms of words and scenes related to the two concerns of unfair treatment. This study found eight data of gender discrimination and ten data of racial discrimination that were obtained by the three African-American women characters of Hidden Figures film. The result of this study showed that: (1) Katherine obtained the treatments of gender discrimination through educational and cultural aspects and racially discriminated through the institutional and ultimately teleological racisms; (2) Dorothy obtained the gender discrimination treatments through the aspect of culture and racially discriminated by the institutional and ultimately teleological racisms; and (3) Mary obtained the gender discrimination treatments through the educational, cultural, and racial aspects and racially discriminated by the institutional racism. This study concludes that the three African-American women experience unfair treatments in two forms which are the gender discrimination and racial discrimination.